Rubber Seed Shell Based Activated Carbon as Potential Biosorbent for the Removal of Heavy Metals from Aqueous Solution - Rosly, Muhammad Bukhari; Md Ali, Abd Halim; Aminallah, Nomie Marini; Hamzah, Muhammad Hazwan; Azhari, Ahmad Hazwan; Shamsulbahrin, Shahirah; Abdul Rahim, Mohamad Akmal (International Journal of Integrated Engineering, 2025)
Heavy metals contamination in water body and aquatic ecosystems has significantly affects and posing serious threats to the environment, aquatic life, and public health. Due to its widespread occurence and harmful effects, adressing this issues remains a critical challege. This study explores the utilization of a widely available agricultural by-product in Malaysia such as rubber seed shells (RSS), as a raw material for producing low-cost activated carbon (AC) for heavy metal removal applications. To enhance the surface porosity and adsorbent characteristics, the RSS was chemically activated using sodium hydroxide (NaOH) and carbonized. Scanning Electron Microscopy (SEM), Fourier Transform Infrared Spectroscopy (FTIR), and X-ray Diffraction (XRD) analyses was carried out to characterized the rubber seed shell ras sample (raw-RSS) and rubber seed shell activated carbon (RSS-AC), respectively. The removal efficiency of lead (Pb) and copper (Cu) were evaluted via batch biosorption test under varying conditions of initial concentration (200 - 800 ppm), contact time (15 - 60 min), and biosorbent dosage (0.05 - 0.20 g). Results shows that under optimum conditions of 200 ppm initial concentration, 60 minutes contact time, and 0.20 gram biosorbent dosage yielded removal efficiencies of 77.45% for Cu and 99.20% for Pb. These results highlight that rubber seed shell based activated carbon as an effective, eco-friendly biosorbent for wastewater treatment.